Differential Effects of Serum Lipoprotein-Associated Phospholipase A2 on Periventricular and Deep Subcortical White Matter Hyperintensity in Brain - Jiang, Junying; Gao, Yuanyuan; Zhang, Rui; Wang, Lin; Zhao, Xiaoyuan; Dai, Qi; Zhang, Wei; Xu, Xiujian; Chen, Xuemei (Frontiers in Neurology, 2021)
Background and Purpose: Serum level of lipoprotein-associated phospholipase A2 (Lp-PLA2) was associated with white matter hyperintensity (WMH). There were differences in the anatomical structure and pathophysiological mechanism between periventricular WMH (PVWMH) and deep subcortical WMH (DSWMH). In this study, we aimed to investigate the effects of serum Lp-PLA2 on the PVWMH and DSWMH. Methods: In total, 711 Chinese adults aged ≥45 years with cranial magnetic resonance imaging (MRI) were recruited in this cross-sectional study, who had received physical examinations in the Department of Neurology, the Affiliated Jiangning Hospital of Nanjing Medical University due to dizziness and headaches between January 2016 and July 2019. Enzyme linked immunosorbent assay (ELISA) was utilized to determine the serum Lp-PLA2. Fazekas scale was used to measure the severity of PVWMH (grade 0–3) and DSWMH (grade 0–3) on MRI scans. Ordinal regression analysis was carried out to investigate the relationship between serum Lp-PLA2 and PVWMH or DSWMH. Results: Finally, 567 cases were included in this study. The average level of serum Lp-PLA2 was 213.35±59.34 ng/ml. There were statistical differences in the age, hypertension, diabetes mellitus, atrial fibrillation, lacunar infarction, Lp-PLA2 grade, creatinine, Hcy, and H-CRP (P < 0.05) in PVWMH groups. Ordinal regression analysis indicated that there was a lower risk of PVWMH in the patients with normal and moderately elevated serum Lp-PLA2 compared with those with significantly elevated serum Lp-PLA2 after adjusting age, hypertension, diabetes mellitus, atrial fibrillation, lacunar infarction, Cr, Hcy, and H-CRP. In addition, PVWMH was correlated to advanced age, hypertension, diabetes mellitus, and lacunar infarction. After adjusting for confounding factors, DSWMH was correlated to advanced age and lacunar infarction. There was no correlation between serum Lp-PLA2 and DSWMH. Conclusions: Serum Lp-PLA2 was closely associated with the pathogenesis of PVWMH rather than DSWMH. There might be different pathological mechanisms between PVWMH and DSWMH.